2016
DOI: 10.1111/jtxs.12230
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of pH and heating conditions on the physical properties of Alaska pollock surimi gels

Abstract: The uniqueness of this study was to measure the combined effect of pH and heating conditions on the gel texture and color. There were various studies dealing with pH or heating conditions independently. As the primary character for surimi seafood is gel texture and color. The highest values of gel strength and deformability, as shown by breaking force and penetration distance, were obtained at pH 7.5-8.0, while the lowest values were at pH 10.0 followed by pH 6.0 and pH 6.5, respectively. Two-step slow heating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The above results could be attributed to lower protein solubility or the changes in the α‐helix conformation of myosin rod segments, which is crucial for the formation of the heat‐induced gels (Ishioroshi, Samejima, Arie, & Yasui, ). Present results were consistent with the report of Lee et al (), who demonstrated the association between the gel strength and pH of surimi paste.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The above results could be attributed to lower protein solubility or the changes in the α‐helix conformation of myosin rod segments, which is crucial for the formation of the heat‐induced gels (Ishioroshi, Samejima, Arie, & Yasui, ). Present results were consistent with the report of Lee et al (), who demonstrated the association between the gel strength and pH of surimi paste.…”
Section: Resultssupporting
confidence: 94%
“…Surimi paste was obtained after mixing with cold ion‐exchange water (IEW) and NaCl. The pH of surimi paste was adjusted from 5.5 to 9.5 by addition of chilled 2 M HCl or 2 M NaOH (Lee et al, ). After evenly mixing, fish oil was added according to one‐tenth of the quantity of surimi paste.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering gel strength of surimi samples, it may be concluded that higher salt concentration resulted in higher gel strength, most probably due to potential role of salt ions as binding aid among protein structures. Lee et al (2016) studied combined effect of pH and heating conditions on physical properties of surimi gels of Alaska Pollock. Surimi dough was prepared at different pH values (4.0-10.0) and a two-step heating was applied.…”
Section: Yield and Some Quality Parameters Of Surimimentioning
confidence: 99%
“…There are many intrinsic and extrinsic factors that could affect fish spoilage and lead to lipid and protein oxidation such as transition metal ions, haem pigments (Wu et al., 2017; Yin et al., 2017), temperature (Lee et al., 2017), and pH. Among them, environmental pH is considered an important parameter affecting the pro‐oxidative ability of Hb and tends to enhance the lipid and protein oxidation (Rummer et al., 2013).…”
Section: Introductionmentioning
confidence: 99%